Aerosol drug‐delivery and short‐term clinical outcomes of suboptimal peak inspiratory flow rate in chronic obstructive pulmonary disease. Issue 12 (22nd September 2021) - Harb, Hadeer S.; Ibrahim Laz, Nabila; Rabea, Hoda; Madney, Yasmin M.; Boshra, Marian S.; Abdelrahim, Mohamed E. A.
Abstract: Aim of work: Suboptimal peak inspiratory flow rate (PIFR) is highly prevalent in chronic obstructive pulmonary disease (COPD) patients owing to the mismatch of their own PIFR with the corresponding inhaler‐device resistance. This study aimed to evaluate aerosol drug‐delivery and short‐term clinical outcomes of suboptimal PIFR in COPD subjects. Methods: Twenty optimal and suboptimal COPD subjects were crossed over in this prospective, randomised, controlled, open‐label study. They were tested for urinary salbutamol amount (USAL30) and spirometric response 30 min poststudy dose (200 µg salbutamol) through Aerolizer ® and Handihaler ® after assessment of their own PIFR through In‐Check™ Dial G16. Urine samples were extracted through solid‐phase extraction and assayed through a high performance liquid chromatography (HPLC) method. Results: Mean USAL30 was significantly higher in the optimal group than in the suboptimal group ( P  = .001). There was no significant difference in ΔFEV1% predicted and ΔFVC% predicted between optimal and suboptimal groups, with higher values in optimal Aerolizer ® and Handihaler ® than in suboptimal groups. Conclusion: Suboptimal PIFR was associated with a significantly lower drug delivery in COPD subjects at hospital discharge, and a slightly lower pulmonary function response 30 min postbronchodilation if compared with optimal PIFR.